2006
DOI: 10.1016/j.jmr.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cryogenic probes as a function of ionic strength and sample tube geometry

Abstract: The pursuit for more sensitive NMR probes culminated with development of the cryogenic cooled NMR probe. A key factor for the sensitivity is the overall resistance of RF circuitry and sample. Lowering the coil temperature to approximately 25 K and the use of superconducting coil material has greatly reduced the resistance contribution of the hardware. However, the resistance of a salty sample remains the same and evolves as the major factor determining the signal-to-noise ratio. Several approaches have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 43 publications
0
57
0
Order By: Relevance
“…Additionally, due to several pK a values, this buffer is also applicable to the study of acid unfolded proteins. In general, buffer and salt concentration should be kept low as the ionic strength decreases the sensitivity of especially cryogenic NMR probes (24). This is particularly important for polyionic buffers such as phosphate (25).…”
Section: Sample Preparationsmentioning
confidence: 99%
“…Additionally, due to several pK a values, this buffer is also applicable to the study of acid unfolded proteins. In general, buffer and salt concentration should be kept low as the ionic strength decreases the sensitivity of especially cryogenic NMR probes (24). This is particularly important for polyionic buffers such as phosphate (25).…”
Section: Sample Preparationsmentioning
confidence: 99%
“…For example, a 400 mM phosphate buffer was sufficient for buffering the aqueous solution of metabolites from 25 mg of lyophilized tomato powder [5,9]. On a different note, a relevant loss of sensitivity was observed when a high buffer concentration was used, particularly with cryogenically cooled probes [19]. The phosphate buffer is a suitable one for NMR applications because it has only exchangeable protons that do not produce additional 1 ) present in plant tissue extracts.…”
Section: Sample Preparation For the Nmr Analysismentioning
confidence: 99%
“…At present, commercial probes are restricted to solution -state NMR, although cryogenically cooled HR -MAS and solid -state NMR probes are in development. In an organic solvent system, cryogenically cooled probes provide a three -to fourfold enhancement in sensitivity (Kim et al, 1995 ;Odoj et al, 1998 ;Voehler et al, 2006 ). This advantage decreases as the salinity of the sample increases.…”
Section: Cryogenically Cooled Probesmentioning
confidence: 99%
“…This advantage decreases as the salinity of the sample increases. It has been recently shown that with samples that have > 4 M NaCl, the use of a smaller diameter temperature probe (1 -4 mm) can be advantageous over a cryo -probe, especially for " mass limited " samples (Voehler et al, 2006 ). However, in NOM research, the sample is often not limited (i.e., at least 50 mg of sample is available).…”
Section: Cryogenically Cooled Probesmentioning
confidence: 99%